Healthcare Providers' Vaccination Against COVID-19: Safety Concerns - Rezaee, Elham; Ali Asgarzadeh, Shafagh; Ali Asgarzadeh, Javad; Farhadi, Ghazale; Mikaeili Mirak, Sevda (International Pharmacy Acta, 2024)
This study examined parameters that may affect the severity and type of side effects associated with COVID-19 vaccine administration at Imam Khomeini Hospital in Ardabil, Iran. Based on a reliable and valid questionnaire, data were collected from 149 hospital employees at random. 77.2% of the study participants were women, and 52% were between the ages of 30-39. Approximately 50% of the participants had a healthy body mass index. Of the participants, 76.5% had no underlying disease. The prevalence of complications after injection of the first dose (regardless of vaccine type) included fever (45%), chills (28.3%), injection site complications (34.9%), myalgia (46.3%), weakness and fatigue (43%), headache (24.2%), thrombocytopenia (1.3%), cough (4%), nausea (6.7%), diarrhea (6.7%), and other complications (5.4%). After receiving a second dose, the most frequently reported adverse reactions were fatigue and weakness. This pattern was repeated for third dose. Injection of the first dose of vaccine induced the most severe side effects. The results demonstrated a significant relationship between severity and duration of side effects and participants' age, sex, body mass index, diet quality, physical activity, and complementary medicines. Participants with underlying health conditions and those using corticosteroids had higher adverse effects incidences. A significant positive correlation (0.878%) was observed between fever severity and chills. SputnikV and AstraZeneca vaccines were associated with more side effects. In general, the rate and severity of side effects after vaccination are directly related to female gender, low body mass index, previous infection, and young age.